Efficacy of Imiflex, Zest, and Assure II on Green Foxtail Control - V. Kumar; I. Effertz; T. Lambert; R. Liu; B. Bean (Kansas Agricultural Experiment Station Research Reports, 2021)
Grass weeds pose a serious management challenge in grain sorghum. Recent development of three herbicide-tolerant grain sorghum technologies such as Inzen, Igrowth, and DoubleTeam will provide the opportunity for producers to use nicosulfuron (Zest), imazamox (Imiflex), and quizalofop-p-ethyl (FirstAct) for grass weed control, respectively. The main objectives of this research were to (1) determine the effectiveness of Imiflex applied preemergence (PRE) on green foxtail control in comparison to commonly used group 15 herbicides; (2) compare the efficacy of Zest, Imiflex, and Assure II applied early- or late-POST at two different rates; and (3) determine the tank-mix compatibility of Zest, Imiflex, Assure II, and Select Max (clethodim) with 2,4-D (Weedar 64) and dicamba (Clarity) on green foxtail control. Field experiments were conducted in fallow ground with a natural infestation of green foxtail at Kansas State University Agricultural Research Center in Hays, KS. PRE herbicide programs, including Imiflex, Dual II Magnum, Warrant, and Outlook were tested. Imiflex, Zest, and Assure II were tested in early- or late-postemergence (POST) timings. The early POST treatments of Imiflex, Assure II, Zest, and Select Max alone or in tank-mixture with Weedar 64 and/or Clarity were also tested in a separate study. Among PRE programs, Imiflex tested at both rates provided an excellent control (89 to 94%) of green foxtail up to 50 days after PRE (DAPRE), whereas control did not exceed more than 51% with any of the group 15 herbicides. Among early POST programs, Assure II at 10 fl oz/a provided 95% green foxtail control at 28 days after early POST (DAEPOST). Green foxtail control with early POST treatments of Imiflex, Zest, and Assure II (6 oz/a) was moderate and ranged from 77 to 83% at 28 DAEPOST. Green foxtail control with late POST treatments of Imiflex, Zest, and Assure II was inadequate and ranged from 14 to 31% at 21 days after late POST (DALPOST). In a separate study, tank-mixing Weedar 64 or Clarity with Assure II reduced the efficacy by>50% on green foxtail control compared to Assure II alone treatment. These results suggest that PRE applied Imiflex (6 or 9 oz/a) can provide excellent residual activity for early season control of green foxtail. Furthermore, Assure II applied early POST at a higher rate can provide effective control of green foxtail; however, the efficacy will significantly decline if Assure II is tank-mixed with Weedar 64 or Clarity.
Keywords: Assure II; green foxtail; herbicide-tolerant sorghum; Imiflex; Zest